Newly discovered population of Bumpy Glassfrog, Centrolene heloderma (Duellman, 1981), with discussion of threats to population persistence - Katherine L. Krynak; Dana G. Wessels; Segundo M. Imba; Jane A. Lyons; Juan M. Guayasamin (Check List, 2018)
Since 2011, the Bumpy Glassfrog, Centrolene heloderma (Duellman, 1981) was known only from a single location in the Mindo region of Ecuador. We report a newly discovered population located in the area of La Sierra, along Río Alambi, a stream system used heavily for aquaculture of rainbow trout (Oncorhyncus mykiss). Threats to population persistence include anthropogenic habitat disturbances such as agriculture and aquaculture, and Batrachochytrium dendrobatidis infection. To improve conservation outcomes, we include notes on C. heloderma natural history, Batrachochytrium dendrobatidis susceptibility, and discuss possible mitigation strategies to protect the species.